Pengaruh Pendapatan Asli Daerah, Dana Bagi Hasil, Dana Alokasi Umum dan Dana Alokasi Khusus terhadap Belanja Daerah dan Pertumbuhan Ekonomi (Studi Kasus pada Kabupaten/Kota di Provinsi Kalimantan Selatan Tahun 2010-2019) - Firda Monica; Chairul Sa’roni (PPJP Universitas Lambung Mangkurat, 2022)
This study was conducted to analyze the effect of PAD, DBH, DAU, DAK on Regional Expenditures and Economic Growth. This research was conducted in all regencies/cities in South Kalimantan Province within a period of 10 years, namely from 2010-2019. The data used is secondary data obtained from the Central Statistics Agency (BPS) and the website of the General Directorate of Balance (www.djpk.kemenkeu.go.id). The type of data studied is panel data with an analytical method that is path analysis. The results showed that PAD, DBH, DAU, and DAK had a significant effect on Regional Expenditures. PAD and Regional Expenditures have a significant effect on Economic Growth. Meanwhile, DBH, DAU, and DAK do not have a significant effect on Economic Growth. Regional Expenditures can be a mediator between PAD, DBH, DAU, and DAK on Economic Growth.